Expresión xvy⇒(x=y)
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
x⇔y=(x∧y)∨(¬x∧¬y)(x∨y)⇒(x⇔y)=(x∧y)∨(¬x∧¬y)
(x∧y)∨(¬x∧¬y)
Tabla de verdad
+---+---+--------+
| x | y | result |
+===+===+========+
| 0 | 0 | 1 |
+---+---+--------+
| 0 | 1 | 0 |
+---+---+--------+
| 1 | 0 | 0 |
+---+---+--------+
| 1 | 1 | 1 |
+---+---+--------+
(x∨¬x)∧(x∨¬y)∧(y∨¬x)∧(y∨¬y)
(x∨(¬x))∧(x∨(¬y))∧(y∨(¬x))∧(y∨(¬y))
(x∧y)∨(¬x∧¬y)
(x∨¬y)∧(y∨¬x)
Ya está reducido a FND
(x∧y)∨(¬x∧¬y)